Avaliação da adesão, índice de complexidade de medicamentos e técnica de uso de dispositivos inalatórios em pacientes com doença pulmonar obstrutiva crônica - Diniz, Nayara Otaviano (2014)
Chronic obstructive pulmonary disease is a common, avoidable and treatable disease characterized by persistent obstruction of the airways and lungs. This disease is usually progressive and associated with a chronic inflammatory response set off by noxious particles or gases. Patients with chronic obstructive pulmonary disease, represents a great impact on the increase of clinical care, as well as the economic health spending to provide better quality of life. This study characterizes the pharmacoepidemiological profile, adherence to drug therapy, pharmacotherapy complexity and performance of using inhalation devices in outpatient’s subjects of a referral hospital for treatment of pulmonary diseases. This is a descriptive, exploratory and transversal study. 83 individuals were interviewed, with a predominance of males, a mean age of 68.22 years, and low schooling. The average number of medications per patient was 5.58, characterizing the polypharmacy, and 81.9% had some type of comorbidity. The founded prevalence was mean adherence rate (45.8%). The most frequent response among the questions asked to measure adherence was related to forgettings (38.6%). The complexity therapy had a mean value of 15.9 points, a high score that reveals the difficulties in following the treatment. After evaluation of inhalation devices was found that as the use of dry powder inhaler Aerolizer, the technique was considered good in 62.5% of patients, the use of Respimat ® inhaler was "good" in 70.96% of cases and the use of metered-dose aerosol showed to be regular in 64.7%. The evaluation of the use of the devices found flaws in several steps considered essential for their proper management. From these data, are needed strategies that aimed at enhancing actions to improve adherence to therapy and ongoing evaluation of inhalation devices, minimizing complications for the patient.